Evaluasi Kualitas Perangkat Lunak Menggunakan ISO/IEC 9126-4 Quality In Use (Studi Kasus : FILKOM Apps) - Victor Axelius Kristianto Siren; Nanang Yudi Setiawan; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
FILKOM Apps is an application with a web platform that is used for the processing of bachelor thesis. From the results of interviews conducted to undergraduate students taking thesis courses it is known that most do not know in detail the process of working on a thesis involving FILKOM Apps. To find out the extent to which FILKOM Apps has met the expectations and goals of use of students in the context of the work of the thesis, a quality evaluation is needed. To conduct a quality evaluation, it will refer to the standard ISO / IEC 9126-4 Quality In Use. According to ISO / IEC 9126-4 standardization, Quality In Use for evaluating quality can use four characteristics, namely Effectiveness, Productivity, Safety, and Satisfaction with the metrics on each characteristic. From the weighting results it is known that the characteristics used in evaluations are Effectiveness and Productivity. Then an evaluation is carried out in the form of a user test for students. As a parameter of success refer to the metrics for the characteristics of Effectiveness and Productivity. From the measurement results of the characteristics of the Effectiveness metric Task Effectiveness and Completion The average task is 0,97, the average Frequency of Errors is 0,07 and the characteristics of Productivity Average Processing Time is 33.30 seconds, the Average Task Efficiency metric is 5.3% , the Earning Proportion metrics averaged 66%, and the metrics of Relative Efficiency of Users averaged 54%. From the evaluation results get a good rating, because all of them are in accordance with the range set by ISO / IEC 9126-4 Quality In Use.